O papel da transglutaminase-2 na proteção de alterações vasculares estruturais e funcionais induzidas pelo envelhecimento em camundongos nocaute - Armstrong, Dinani Matoso Fialho de Oliveira [UNIFESP] (2017)
BACKGROUND: Vascular aging is associated with changes in arterial wall structure and function, that will contribute to the development of vascular stiffness and endothelial dysfunction. It has recently been demonstrated that tissue transglutaminase (TG2) plays a role in vascular stiffening associated with aging. OBJECTIVE: We sought to determine whether the absence of TG2 enzyme in TG2 knockout mice (TG-/-) protect them against early age-related functional, histological immunohistochemical arterial changes. METHODS: We used 20 TG-/- male mice and 20 wild type male mice as control (CT), line BL6/129S. From each species, 10 were 8 months of age (old TG-/- and old CT) and 10 were 3 months of age (young TG-/- and young CT), forming 4 experimental groups. Pulse wave velocity (PWV) and mean arterial pressure (MAP) were measured non-invasively. Thoracic aortas were removed for evaluation of endothelial dysfunction, as well as histological and immunohistochemical analyzes. RESULTS: PWV and MAP TG-/- mice were similar to CT for age-matched mice (PWV TG-/- elderly 4,44 ± 0,20 vs. CT elderly 3,85 ± 0,2, n=10, p=0,06; MAP TG-/- elderly 78,23 ± 4,77mmHg vs CT elderly 83,69 ± 5,37 mmHg, p=0,45, n=10). Old CT mice exhibited a markedly attenuated vascular relaxation as compared to Young CT animals (CT old 54.48% ± 5 vs. CT young 72.11% ± 2, p < 0.001; TG-/- old 70.55% ± 4 vs. TG-/- young 92.87 ± 6, p = 0.001). The TG-/- young and old mice had enhanced vasorelaxation responses (p<0.01) as compared to control mice. SNP dose response curve demonstrates no significant differences in endothelial independent responses to sodium nitroprusside. There was a significant increase in TG2 crosslinks by immunohistochemistry in CT old group compared to young (3,66 ± 0,33 vs 1,33 ± 0,33, p=0,007, n=3), with no stain in the TG-/- animals. Optical microscopy examination of Old CT mice aorta showed thinning and fragmentation of elastic laminae, with cellular infiltrate in media tunica. Young CT mice, old and young TG-/- mice presented the elastic laminae of the tunica media regularly arranged and parallel. CONCLUSION: The genetic suppression of TG2 delays the age-induced endothelial dysfunction and histological modifications. These findings appear to precede changes in noninvasive functional parameters such as pulse waveform and blood pressure.